Pollution assessment of organochlorine pesticides in urban agricultural soils of Jilin City, China. Issue 3 (2nd April 2016) - Zhang, Jingjing; Liu, Jingshuang; Yu, Rui; Liu, Qiang; Wang, Yang
ABSTRACT: The content, source, and pollution level of organochlorine pesticides (OCPs) in soils are necessary to assess potential risks to eco-environment and human health, and to target environment-friendly policies. A total of 50 surface soil samples were collected from urban vegetable fields of Jilin City and thirteen OCPs were analyzed. The concentrations were in the ranges of 3.16–48.35 ng·g −1 for Dichloro-Diphenyl-Tricgloroethanes (DDTs, sum of o, p′-DDT, p, p′-DDT, p, p′-DDD, and p, p′-DDE), 4.37–44.77 ng·g −1 for Hexachlorocyclohexanes (HCHs, sum of α-HCH, β-HCH, γ-HCH, and δ-HCH), 1.19–13.17 ng·g −1 for Chlordanes (sum of heptachlor, t-chlordane, and c-chlordane), 0.24–2.60 ng·g −1 for aldrin, and nd–3.43 ng·g −1 for dieldrin, respectively. The different compositions indicated that the residues of DDTs and HCHs originated mainly from the historical application, while chlordanes were mostly from recent input. On the basis of soil quality standards of China and the Netherlands, DDTs and chlordanes in this study were categorized as light pollution, and HCHs were classified as no pollution for the majority of soil samples. There are a variety of OCPs residues in urban vegetable soils of Jilin City, but it is still safe and suitable for agricultural production.